PENGAKUAN, PENILAIAN DAN PENGUNGKAPAN “ASET” SATWA DI LEMBAGA KONSERVASI - Muhammad Irfan Dermawan; Warsito Kawedar (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to find the normative method of recognition, assessment, and disclosure of animals as assets managed by conservation institutions. This research choose Semarang Zoo as one of conservation insitutions of protected animals in Indonesia.This research is using primary data based on deep interview with interviewee who are representatives of Semarang Zoo, Natural Resources Conservation Center, and academics from the Diponegoro University Accounting Department. This research is using analysis method with procedure of data collection, data condensation, data display, and drawing and verifying conclusions.The research conclude that until now there’s still differences of opinion in the recognition, assessment, and disclosure of animals as assets which is the whose ownership is in the hands of the government which is stated in UU No. 5 of 1990 about Conservation of Biological Resources and their Ecosystems. The recognition, assessment, and disclosure of preserved animals corpes are still in question.